Cybercrime and dark web in Africa - Gulyás, Attila (Journal of Central and Eastern European African Studies, 2025)
The widespread availability of smart devices and internet access has radically transformed the continent’s cybersecurity landscape. However, this sudden technological change was not accompanied by the development of a robust cybersecurity infrastructure. State actors, economic operators, and the population were unprepared for the risks associated with new technology. Criminals have taken advantage of this situation, resulting in various types of cyberattacks against actors in economic life, state institutions, critical infrastructures, and the population. The author hypothesized that there is a correlation between cybercrime rates and dark web usage in African countries. To test this hypothesis, quantitative data was collected on internet penetration, cybercrime statistics, and dark web usage. The analysis of the collected data confirmed the hypothesis that there is a correlation between a country's use of the dark web and the severity of cybercrime.